Effects of storage conditions on the stability of spray dried, inhalable bacteriophage powders - Leung, Sharon S.Y. (Int J Pharm, 2017)
This study aimed to develop inhalable powders containing phages active against antibiotic-resistant Pseudomonas aeruginosa for pulmonary delivery. A Pseudomonas phage, PEV2, was spray dried into powder matrices comprising of trehalose (0–80%), mannitol (0–80%) and L-leucine (20%). The resulting powders were stored at various relative humidity (RH) conditions (0, 22 and 60% RH) at 4 °C. The phage stability and in vitro aerosol performance of the phage powders were examined at the time of production and after 1, 3 and 12 months storage. After spray drying, a total of 1.3 log titer reduction in phage was observed in the formulations containing 40%, 60% and 80% trehalose, whereas 2.4 and 5.1 log reductions were noted in the formulations containing 20% and no trehalose, respectively. No further reduction in titer occurred for powders stored at 0 and 22% RH even after 12 months, except the formulation containing no trehalose. The 60% RH storage condition had a destructive effect such that no viable phages were detected after 3 and 12 months. When aerosolised, the total lung doses for formulations containing 40%, 60% and 80% trehalose were similar (in the order of 10(5) pfu). The results demonstrated that spray drying is a suitable method to produce stable phage powders for pulmonary delivery. A powder matrix containing ≥ 40% trehalose provided good phage preservation and aerosol performances after storage at 0 and 22 % RH at 4 °C for 12 months.